Pengaruh Relationship Marketing dan Suasana Cafe Terhadap Loyalitas Pelanggan Aloka Kopi Kota Tebing Tinggi dengan Kepuasan Sebagai Variabel Intervening - Nur Aisyah Auliya; Desi Safitri Ani; Eka Mayastika Sinaga; Limega Chandrasa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of Relationship Marketing and Cafe Atmosphere on Customer Loyalty of Aloka Kopi Tebing Tinggi City with Satisfaction as an Intervening Variable. The research assistance method used is a quantitative method using Smart PLS to analyze data. The research population is customers who have visited more than once and the results obtained are 92 people for the research sample. The results of this study are Relationship Marketing has a positive effect on Customer Satisfaction. Cafe Atmosphere has no effect on Customer Satisfaction Relationship Marketing has a positive effect on Customer Loyalty. Cafe Atmosphere has a negative effect on Customer Loyalty. Customer Satisfaction has a positive effect on Customer Loyalty. Relationship Marketing has a positive effect on Customer Loyalty with Customer Satisfaction as an intervening variable. Cafe Atmosphere has a positive effect on Customer Loyalty with Customer Satisfaction as an intervening variable.